Peningkatan Keterampilan Menulis Melalui Media Gambar - Wardiman Wardiman (Universitas Islam Negeri Imam Bonjol Padang, 2010)
Skill of poetry writing as one part of language skills and compose literature, need to be taught in secondary school. It is stated in the curriculum of Indonesian 2004. However, based on field observations, students' ability to write poetry is still low. On average 87% of students have not achieved minimum mastery standard (SKBM). This is due to a lack of student motivation in writing poetry. Besides, have not found the right method or media in an effort to improve the ability to write poetry. Therefore, through the use of media images of poetry student writing skills can be improved. This study aims to enhance students' skills in writing poetry through the medium of drawing. The research is classroom action research. The results of this study to demonstrate that students' skills in writing poetry can be enhanced through media images. The implications of this research is necessary the implementation of media images for learning to write poetry because it can increase the kemmapuan students in writing poetry and activities of students in learning.